A Randomized Trial Comparing The Effect of Soy Protein Diet Supplement Versus Hospital Standard Supplement on Clinical and Laboratory Parameters in Malnutrition Patients - Ari Fahrial Syam; Marcellus Simadibrata; Chudahman Manan; Daldiyono Hardjodisastro; Riadi Wirawan; Helsi Helsi (The Indonesian Society for Digestive Endoscopy, 2003)
Background: Studies have shown that soy protein diet may improve clinical nutrition status of malnutrition patients. Soybeans itself are unique foods because of their rich nutrient content. The complete nutrient in soybean is important and also offers many health benefits especially in malnutrition patient during hospitalization. Objective: The objective of this study was to assess the effect of soy protein supplement and hospital standard supplement (animal protein) on anthropometries and laboratory findings in malnutrition patients during hospitalization. Method: Forty-eight patients with malnutrition (confirmed by Body Mass Index 20 kg/m2) aged 14- 70 years old were recruited from Internal Medicine wards in Cipto Mangunkusumo hospital, Jakarta, Indonesia. The study design was randomized controlled trial. The subjects were randomly divided into 2 groups were fed supplement diet contained soy protein supplement diet (40 g/d) or hospital standard supplement (40 g/d) for 2 weeks. Body weight was measured in the first day (base line data), 7-dayand 14-day after intervention. Blood and urine was collected at baseline, 7-day and 14-day for measuring transferin, prealbumin and nitrogen balance. The intake of supplement, gastrointestinal symptoms and others adverse event were noted every day. Result: From 48 subjects, there were only 32 patients that completed the study during 2 weeks. In the base line data there were no significant different for intake diet calculation, anthropometrics and laboratory parameters in study group and control group. A total of patients 32 consist of 20 (62,5 %) female and 12 (37,5%) male with a mean age 31,8 + 12,9 years old. Anthropometrics evaluation after 1 week and 2 weeks intervention in soy protein supplement showed significantly increased every week in 2 weeks. In control group, significantly increased showed only after two weeks intervention. But there was no significantly increased of BMI of two groups. Serum transferin concentration increased from 1,489 ± 0,502 at base line to be 1,600 ± 0,502 at week 1 and to bel, 695 ± 0,402 in study group. But this increasing was no significantly between two groups. No significant differences were found between two groups for prealbumin level after 1 week and 2 weeks intervention. Nitrogen balance improved significantly (p0,05) more with soy protein supplement than hospital standard supplement (animal protein). In this study, there was no side effect in soy protein supplement diet and 1 case with diarrhea and nausea in hospital standard supplement (animal protein) Conclusion: Soy protein supplement diet improved both of nutrition parameter: anthropometrics and laboratory parameter. There were no significantly different in anthrometrics and laboratory parameter berween soy protein supplements tahan hospital standar supplement (animal protein). But nitrogen balance improved significantly in study group than control group. Substitution of soy protein for animal protein has the potential role for the patient with malnutrition Keywords: Soy protein diet, Malnutrition